Risky Killing: How Risks Worsen Violations of Objective Rights - Lazar, Seth (Journal of moral philosophy, 2019)
I argue that riskier killings of innocent people are, other things equal, objectively worse than less risky killings. I ground these views in considerations of disrespect and security. Killing someone more riskily shows greater disrespect for him by more grievously undervaluing his standing and interests, and more seriously undermines his security by exposing a disposition to harm him across all counterfactual scenarios in which the probability of killing an innocent person is that high or less. I argue that the salient probabilities are the agent’s sincere, sane, subjective probabilities, and that this thesis is relevant whether your risk-taking pertains to the probability of killing a person or to the probability that the person you kill is not liable to be killed. I then defend the view’s relevance to intentional killing; show how it differs from an account of blameworthiness; and explain its significance for all-things-considered justification and justification under uncertainty.